Mental health status of infertile couples based on treatment outcome - Mohammad Hosein Baghianimoghadam; Amir Hossein Aminian; Behnam Baghianimoghadam; Nasrin Ghasemi; Ali Mohammad Abdoli; Najmeh Seighal Ardakani; Hosein Fallahzadeh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Infertility is accompanied by numerous psychological and social problems. Infertile couples are more anxious and emotionally distressed than other fertile people. Previous studies suggested that infertility is more stressful for women than men. Objective: The purpose of this study was to determine the status of general health of infertile couples. Materials and Methods: This cross-sectional study evaluated general health of 150 infertile couples attending to Yazd Research and Clinical Center for Infertility that were selected consequently. The data were gathered by the researchers, based on face to face interview before and after three months of treatment by two questionnaires. The first questionnaire had questions on demographic information and the second one was the General Health Questionnaire-28 (GHQ-28). This questionnaire has four sub- scales areas. All data were transferred directly to SPSS 15 and analyzed. Results: The mean age of women was 28.3 and men were 32.4 years. The scores for all sub- scales of GHQ in women were more than men. There was significant difference between age and general health at physical symptoms scales (p=0.002), anxiety and sleep disorders (p=0.003). The age group 25-29 years had higher scores (more than 7) than other age groups. There was significant difference between the scale of social dysfunction and results of treatment. Conclusion: Our results, similar to the previous studies have revealed negetive social and mental effects of infertility on women is more than men, so there is need that they be educated specially.